Jihadist visual communication strategy: ISIL's hostage executions video production. (November 2019) - Herfroy-Mischler, Alexandra; Barr, Andrew
Based on a visual, verbal and aural quantitative and qualitative content analysis of the 62 execution videos produced by the Islamic State of Iraq and the Levant (ISIL) during its first year of existence (2014–2015), the aim of this research is to further the understanding of the inherent nature of the narratives spread by ISIL execution videos and to which audience(s) they are targeted. The authors adopt a bottom-up systematic approach of coding based on grounded theory to process visual and aural communication data as well as verbal communication of more than seven hours of ISIL hostage execution videos. In so doing, this research contributes to the understanding of multimodal communication interactions and the role of their discrepancies in framing fundamentalist ideologies. Moreover, the study adds perspective to previous research on Jihadist visual communication and audience studies. The results demonstrate how hostage execution videos discourse relies on 'framing packages' linked to values, norms and archetypes to create a recurrent and coherent organizational narrative aimed at segmenting ISIL's audiences.